If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 225 = 0 Reorder the terms: 225 + 20x = 0 Solving 225 + 20x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-225' to each side of the equation. 225 + -225 + 20x = 0 + -225 Combine like terms: 225 + -225 = 0 0 + 20x = 0 + -225 20x = 0 + -225 Combine like terms: 0 + -225 = -225 20x = -225 Divide each side by '20'. x = -11.25 Simplifying x = -11.25
| 16=16t^2+16 | | 7n-13=6 | | 7+3(4x-4)=6-5(2x+1) | | x*sqrt(x-3)=4 | | x^2+0.5x-0.01=0 | | 8=8x+8 | | 3+4(5x-6)=6-4(2x+1) | | h(x)=2x^2+x-10 | | x^2-7xy+6y^2= | | y-8=-5(x+1) | | 6=k(12) | | 2.96x-2.6=-3.47x+7.47 | | 10p-3(3p-6)=4(3p-6)-8p | | y=10-2(y-4) | | -18x^2+61xy+7y^2=0 | | 2x^2=6p-20 | | 2z=4z-8 | | 2x^2-6p=-20 | | V-7+1=14+5v | | log5(x^4y^9/6) | | 4x-101=12x-53 | | 7y=4y+9 | | 8-4x=-10+x | | f(x)=senx | | 0.25m+0.75m=2 | | 6x^2-13x+0=0 | | 4x-201=12x-53 | | 5-(-3y)=-9y+3y | | -7/9x=28 | | -4s=-12 | | X^2y-3x^2= | | -18x^2-65xa-7a^2=0 |